Upaya Guru Dalam Mengatasi Kesulitan Membaca Peserta Didik Melalui Media Kartu Huruf Di Kelas III Sd Negeri Lambaro Angan Aceh Besar - Alda Fajar Jasmina; Israwati Israwati; Said Darnius (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2023)
This study aims to describe the teacher's efforts in overcoming students' reading difficulties through the media of letter cards in class III SD Negeri Lambaro Angan Aceh Besar. The approach used in this research is a qualitative approach with a descriptive type of research. The subjects in the study were 10 students who still had difficulty reading in class IIIA and one teacher in class IIIA, with the sampling of data sources carried out by non-probability sampling, namely purposive sampling. Purposive is a sample selection technique with certain considerations. While certain considerations that are intended are reading difficulties experienced by students. Data collection techniques were carried out by observation and interviews. All data from observations and interviews were analyzed through data reduction, data presentation, and conclusion drawing/verification. The results of the study proved that after applying the letter card media to the teacher for three days, it was seen that there was a good change in students' reading ability. The difficulties experienced by students when reading slowly can be resolved properly. During the process of applying the letter card media, the teacher carried out learning activities well, in the application of this letter card media the teacher also explained or introduced simple syllables and sentences to students. Then, the teacher forms groups where students and group members will play letter cards, through this activity students look very enthusiastic in participating in the learning process, especially in learning to read. The letter card media applied by the teacher in the classroom can foster student interest/motivation in learning to read.